Features of distillation separation of multicomponent mixtures - A. K. Frolkova; A. V. Frolkova; V. M. Raeva; V. I. Zhuchkov (Тонкие химические технологии, 2022)
Objectives. To improve the process of developing energy-efficient flowsheets for the distillation separation of multicomponent aqueous and organic mixtures based on a comprehensive study of the phase diagram structures, including those in the presence of additional selective substances.Methods. Thermodynamic-topological analysis of phase diagrams; modeling of phase equilibria in the AspenTech software package using the equations of local compositions: Non-Random Two Liquid and Wilson; computational experiment to determine the column parameters for separation flowsheets of model and real mixtures of various nature.Results. The fractionation conditions of the origin multicomponent mixture due to the use of sharp distillation, pre-splitting process, extractive distillation with individual and binary separating agents were revealed. The columns operation parameters and the energy consumption of the separation flowsheets ensuring the achievement of the required product quality with minimal energy consumption were determined.Conclusions. Using the original methods developed by the authors earlier and based on the generalization of the results obtained, new approaches to the synthesis of energy-efficient multicomponent mixtures separation flowsheets were proposed. The provisions that form the methodological basis for the development of flowsheets for the separation of multicomponent mixtures and supplement the standard flowsheet synthesis plan with new procedures were formulated.